Advantages and Indications for Laparoscopic Cholecystectomy: A Review - Jon Mikel Rementeria Vázquez; Dariana Martinez Marabotto; Brenda Leticia Rodríguez Bonachea; David Martínez Rivera, Yazmín Pérez González; Gabriela Cuéllar Ramírez; Pedro Suárez Loya; Zitlali Rios Ruiz (International Journal of Medical Science and Clinical Research Studies, 2024)
Laparoscopic cholecystectomy quickly became the procedure of choice for treating patients with biliary discomfort and gallstone problems after the initial reports appeared in the late 1980s. Technical advancements, particularly in miniature video cameras and specialized equipment, played a crucial role in the evolution of laparoscopic cholecystectomy. Subsequent improvements in the design and production of instruments and equipment have further enhanced the safety and efficacy of minimally invasive surgery, extending its application to the treatment of various gastrointestinal illnesses, including gallstone disease.